Teacher Methods in Teaching Arabic: A Case Study of One Senior High School in Jambi City - Mohamad Muspawi; Zainul Arifin; Fathin Nadila (Ta'dib: Jurnal Pendidikan Islam, 2017)
This research was conducted in one state senior high school in Jambi city aiming to get the whole picture about the methods of teachers in teaching Arabic vocabulary. We used a qualitative study with a case study approach. The participants of this research were teachers who taught Arabic vocabulary. The data were collected through interviews, documentation, and observation. The results showed that the methods used by the teachers in teaching Arabic vocabulary were mostly lecturing and demonstration. The obstacles faced by the teachers in Arabic vocabulary teaching were covered in several points namely, limited time allocation, teacher education background, infrastructure and lack of student interest in religious learning and expanding Arabic knowledge. We also presented the efforts by teachers to overcome the obstacles such as to motivate the students by telling them the importance of Arabic in international community as one of international students, to give practice tasks implementation, to sustainable evaluation and task.